Assessing the Needs of Interpreter Training in Japan. Issue 2 (November 2014) - Yamada, Naoko
This research attempted to identify the needs present in interpreter training in Japan. Interviews with trainers and interpreters, and questionnaires administered to interpreters were employed to explore (a) the skills and abilities necessary for successful interpreters and (b) the challenges that trainers may experience regarding interpretive training in Japan. The results showed both consistency and inconsistency in the perceptions of interpreters and trainers. Interpretive design, communication and public speaking, and risk management are core subjects recommended for future introductory-level training programs in Japan. Managerial and training skills are suggested for new types of training programs. Several challenges to interpreter training in Japan were also identified.